Clinical Decision Making Over One-Stage versus Two-Stage Implant Technique - Yen, En-Tse (Archive of Orofacial Data Science, 2025)
AIM: This literature review focuses on the success rate, survival rate, soft and hard tissue impact, and complications of one-stage and two-stage implant systems. METHODS: An electronic database search using selected search terms following PICO rules was conducted between December 2021 and January 2022 through PubMed to identify all up-to-date and relevant articles published in the last 10 years in English. A total of 28 articles met the eligibility criteria, which were collected and reviewed for analysis. RESULTS: Of the 28 selected articles for review and systematic analysis, 15 were one-stage dental implant studies, and 13 were two-stage implant reports. The success rate of one-stage implants shown in the studies was slightly lower than that of two-stage implants. Contrarily, the survival rate of one-stage implants was higher than that of two-stage implants. Both soft and hard tissue impacts of one-stage implants were worse than those of two-stage implants. Finally, the complications of the two systems varied in nature and hence cannot be compared quantitatively. CONCLUSION: Two-stage implants should be considered in the aesthetic zone to prevent unwanted gingival and bony resorption. In contrast, the choice of one-stage implant may be more preferable for posterior restoration since oral hygiene can be reinforced before crown cementation.